Trybunał Konstytucyjny w poszukiwaniu legitymizacji. Szkic z socjologii prawa: [The Constitutional Court in search legitimacy: a sketch of sociology of law] (Studia Prawnicze / The Legal Studies, 2015)
Jeffrey Alexander, podążając za myślą jednego z najwybitniejszych socjologów – Émile’a Durkheima stwierdził, że świat społeczny jest zawsze nasycony symbolizmem, a wszystkie współczesne, nawet silnie zsekularyzowane społeczeństwa tworzą święte miejsca, którym przyznają prestiż, autorytet, uznanie1, tym samym zaś prawomocną władzę. W niniejszym artykule autorka chce pokazać, jak tworzy się społecznie uznanie dla polskiego sądu konstytucyjnego. Inaczej rzecz ujmując, jakie procesy sprawiają, że jest on legitymizowaną instytucją prawną, ale nie dlatego, że gwarantują mu ją przepisy prawa, które stosunkowo łatwo mogą przecież ulec zmianie, ale taką, jaką zapewnia wiara, że jest – jak powiedzieliby Peter L. Berger i Thomas Luckmann – „stałym rozwiązaniem stałego problemu danej zbiorowości”. The aim of this paper is to show how the social legitimacy of the Constitutional Court in Poland is constructed. Social legitimacy is considered here in two dimensions. At the macrostructural level the socio-political processes, that led to the creation of the constitutional court are analysed. The microstructural dimension focuses on examining how the individual socio-demographic characteristics of the Constitutional Court’ judges (their scientific degrees, legal practice, political experience and institutions of power), contribute to the strengthening of the Constitutional Court’s position. Thus, the paper argues that the legitimacy of the Court is made by constructing the neutrality of the institution, in particular by locating it in opposition to politics and reinforced by the academic faction of the legal field. The study is based on the sociology of Pierre Bourdieu (and his follower Frédéric Lebaron), as well as inspired by Durkheimian sociology of religion.